IDENTIFIKASI POSISI RUMPON DI LAUT SULAWESI (PROVINSI GORONTALO) - Abdul Wahab, Wulan
The Sulawesi Sea is part of the Fisheries Management Area (WPP) 716 which has abundant fishery potential, so that it becomes the basis for catching economic fish on a small scale and industrial scale. In the waters of the Sulawesi Sea, there are several fishing aids commonly known as Fish Aggregating Devices (FADs). FADs are fish trapping tools that have various shapes and types of binders/attractors from solid objects, which function to attract fish to gather, which is used to increase the efficiency and effectiveness of catching fish. However, having many FADs does not guarantee fish catches. This is because FADs that have been installed can simply be lost by the current of the knife, causing huge losses. In addition, the placement of FADs is a factor in the lack of fish catches by fishermen. Therefore, it is necessary to identify the optimal placement of FADs to determine the optimal location so as to increase the efficiency and effectiveness of fishing. The data used are existing FAD data, Gorontalo province RZWP3K map, submarine cable data, Indonesian Fisheries Potential Zone data, and monthly Sulawesi Sea current models. All these data were processed using the overlay method to determine the optimal location for FAD placement in the Sulawesi Sea area. Based on the results obtained, there were ten FADs that were affected by knife currents throughout 2021. The most frequently affected FADs were Awal +1. These FADs were affected by 11 months of knife currents throughout 2021. In addition, from the results of the analysis related to knife flows, it was found that the moon with the highiest knife current is the month of May. In addition, there is a map related to recommendations for the placement of FADs and also the areas of FADs affected by knife currents.